Trichosporon asahii causing urosepsis: A case report - Subramanian, Pramodhini; Rajendiran, Prabha; Hanifah, Mohammed; Easow, Joshy M (Indian Journal of Case Reports, 2019)
Trichosporonosis is an emerging, life-threatening opportunistic pathogen, implicated in superficial and mucosal infections. However, systemic infections are known to occur in immunocompromised conditions like cancer, burns, transplant patients as well as patients on steroids, peritoneal dialysis, prolonged mechanical ventilation and those undergoing prosthetic valve surgeries. Here, we report the case of Trichosporon asahii isolated from the urine sample of a 69-year-old male patient presented with septic shock. Early diagnosis and management of trichosporonosis which mimic disseminated candidiasis will reduce the mortality rate by selecting appropriate antimicrobial therapy.